General Educational Institutions of Tyumen in 1945–1953 - Elena Borodulina; Artyom Skochin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The aim of the work is to determine the significance of the transformation of the educational process in general educational institutions of Tyumen in the post-war period. In the context of the study, the authors study the expansion of the network and the technical condition of general educational institutions, note changes in the staffing of schools, reveal various aspects of the methodological training of teachers, as well as the process of transforming the educational programs of educational institutions. Methods and materials. The basis of the research work was made up of previously unpublished archival records and statistical materials, regulations that were published as part of collections of documents during the period under study, as well as information from periodicals of the post-war years. In addition, over the past decade, a significant number of regional studies have appeared in historiography concerning the problem of school education in the period under study. Analysis. Soviet education in 1945–1953 was experiencing a serious crisis. School buildings in need of repair, lack of a sufficient number of classrooms and teaching staff, difficult financial and living conditions of general education institutions, difficulties in implementing the law on universal education, increasing requirements for the general education training of students and the teaching activities of teachers – these are not all the problems that Soviet education faced in the post-war period. Results. The researchers come to the conclusion that the post-war years became an important time for the transformation of the educational process in the schools of Tyumen, causing its transition to peacetime. During the study period, the network of educational institutions in the city was expanding, and the number of students was also growing. At the same time, a number of problems remained unresolved, which concerned the low technical condition of educational institutions and multi-shift classes. In the mid-1940s and early 1950s, in the schools of the city, there was an increase in the number, experience, and level of education of teaching staff. Author’s contribution. The search, systematization, and analysis of archival documents, regulations, periodicals, as well as research literature on the topic of research work, followed by composing the main part of the article, was carried out by Candidate of Sciences (History), Associate Professor of the Department of History of Tyumen State University, E.V. Borodulina. Posing general conclusions and checking references was carried out by A.V. Skochin. Funding. The study was carried out with the financial support of the Russian Foundation for Basic Research within the framework of the scientific project No. 20-49-720018.